Analisis Manajemen Laba Pada Laporan Keuangan Perbankan Syariah (Studi Pada Bank Syariah Mandiri Dan Bank Muamalat Indonesia) - Sri Padmantyo (Benefit: Jurnal Manajemen dan Bisnis, 2010)
The aim of this research is to know and analyze : Indication of earning management in financial statement of Bank Syariah Mandiri and Bank Muamalat Indonesia. Researcher uses total accruals from Healy (Arfani and Sasongko, 2005). The resulf of this research is positive of total accruals for four years and negative for one year. It means that there are earning management in financial statement of Bank Syariah Mandiri and Bank Muamalat Indonesia for four years.